Unearthed : the economic roots of our environmental crisis - Sayre, Kenneth M., 1928- (Project Muse philosophy and religion collection., 2010)
"With unerring logic and science, Kenneth Sayre dissects the origins of the ecological crisis and points to the necessary recalibration of industrial societies with the laws of thermodynamics and ecology. It is a radical book in that he gets to the heart of what ails us, and it charts a course toward a future grounded in authentic hope."--David W. Orr, Oberlin College